Indonesia Correlation of Degree of Asthenopia in Corrected and Uncorrected Refractive Errors of 2020 Faculty of Medicine and Health Sciences Students: Korelasi Derajat Astenopia pada Kelainan Refraksi Terkoreksi dan Tidak Terkoreksi Mahasiswa Fakultas Kedokteran dan Ilmu Kesehatan - Ilahi, Luthfiyana; Wihardjo, Erning; Goenawan, Kristian (Jurnal MedScientiae, 2024)
Asthenopia, or what is usually called tired eyes, is the occurrence of tension in the ciliary muscles in the eyes caused by intensive visual activity. The symptoms of asthenopia that are felt are subjective visual discomfort, which causes decreased concentration, academic performance, and work ability. This study aims to determine the correlation between the degree of asthenopia in corrected and uncorrected refractive errors in FKIK Ukrida students in the class of 2020. This study used a total sampling technique with a cross-sectional method with 159 respondents. Data collection was carried out in December. In this study, the number of respondents who had corrected refractive errors consisted of 30 (21.3%) people who did not experience asthenopia, 56 (39.7%) experienced mild asthenopia, 15 (10.6%) people experienced moderate asthenopia, and 1 (0.7%) experienced severe asthenopia. Respondents who had uncorrected refractive errors consisted of 10 (7.1%) people who did not have asthenopia, 13 (9.2%) had mild asthenopia, 14 (9.9%) people, and 2 people did not have severe asthenopia. The degree of asthenopia and the corrected refractive error are correlated, according to the Spearman test findings, with a p-value of 0.032. Symptoms of asthenopia can cause a decrease in visual quality and work ability. The results of this research found that FKIK students experienced more corrected refractive errors. Symptoms of asthenopia are many. Asthenopia is often found in corrected refractive errors. So, education is needed to prevent asthenopia in FKIK students.